Hevristični model razvoja proizvodnih zmogljivosti - Kremljak, Zvonko (Strojniški vestnik, 2005)
Managers in production environments face a high level of uncertainty in their decision making due to the major, rapidly developing changes defining the environments in which their organisations operate. This means that managers donot possess complete information about future events, do not know all the possible alternatives or the consequences of all their possible decisions. Overcoming this uncertainty requires the development of heuristic tools, whichcan offer satisfactory, if not optimal, solutions. Simulation methods based on the extrapolation of available data from the past are unsuitable for help in decision-making processes in uncertain conditions. Lately, the dominant heuristics used for solving decision-making problems during a high level of uncertainty is the theory of real options. For this reason the real-options approach is currently used for an evaluation of the investments in research and development, the development of new products, production technologies and other production sources. As regards engineering, we are witnessing the intensive development of new methods, tools and techniques, which by their origin belong to the field of applied mathematics, information sciences, operational research and economic theory (genetic algorithms, evolution programming, genetic programming, soft logic, neuron networks, the theory of real options, etc.), and are very successfully applied in the solving of various technical optimisation problems. The theory of real optionsis also used in issues related to technology, research and development,and production. The thoughts on the use of the theory of real options have also spread to the area of strategic management.
Keywords: sistemi proizvodni; upravljanje tveganja; teorija stvarnih možnosti; modeliranje negotovosti; mehka logika; proizvodni sistemi; management; upravljanje; hevristične metode